Cerebellar Venous Infarction Combined with Developmental Venous Anomaly and Contralateral Sinus Thrombosis - A. P. Demyanov; M. B. Dolgushin; T. M. Rostovtseva (Вестник рентгенологии и радиологии)
Developmental venous anomalies (DVA) are among the most common malformations, accounting for about 55% of all cerebral vascular anomalies. Most of them are asymptomatic, detected incidentally by brain magnetic resonance imaging and do not require treatment. Complications in DVA are rare. Cases of DVAassociated hemorrhage, venous congestion, and epilepsy have been described in literature; however, most cases of complications are due to other malformations, such as cavernous and lymphatic malformations, focal cortical dysplasias. We present a rare clinical case of infratentorial venous infarction resulting from DVA thrombosis, which was triggered by thrombosis in contralateral sigmoid and transverse venous sinuses.